Severe Acute Respiratory Syndrome Coronavirus-2 Induces Cytokine Storm and Inflammation During Coronavirus Disease 19: Perspectives and Possible Therapeutic Approaches - Mannino, Federica; Bitto, Alessandra; Irrera, Natasha (Frontiers in Pharmacology, 2020)
The new coronavirus outbreak was first identified in Wuhan, China in December 2019, and has turned out to be a global health emergency, affecting millions of people worldwide. Coronavirus Disease 19 (COVID-19), caused by the SARS CoV-2 virus, can manifest with flu-like symptoms and can be complicated by severe pneumonia with acute respiratory distress syndrome (ARDS), however a large percentage of infected individuals do not have symptoms but contribute to the spread of the disease. SARS-CoV-2 infection has become a global public health emergency since no available treatment seems effective and is hard to manage the several complications caused by an intense release of cytokines. This paper reviews the current options on drugs used to reduce the deadly effects of the cytokine storm.